Rancang Bangun Sistem Rekomendasi Tempat Kuliner Khas Malang Berbasis Lokasi - Iqbal Santoso Putra; Ratih Kartika Dewi; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Malang is a place in Indonesia that has a variety of unique culinary. This causing the appearance of places that sell unique culinary and only took place at Malang. However, none of the systems nowadays provide to give the recommendation of unique culinary places that using other criteria aside from using the nearest range. Therefore, we initiating to build a system that gives a recommendation of Malang unique culinary places using more criteria based on location. The system is designed for using TOPSIS to deciding which place will become the best recommendation for the user using four criteria. They are : the nearest range, the cheapest price, the highest rating, and the oldest age. The system will be implemented in the Android application using RESTful web service as data exchange. The test result over the system shows that the system has been implemented using functionals that corresponding with the functionals from the system requirement. TOPSIS algorithm that applied in the system has been stated as valid based on the result of the manual calculation has the same result as the result from the by-system calculation. The test result also stated that the system has been succeeded to approach an A grade with an average score of 81.00. Therefore the system is acceptable for the user.